EFFECTS OF SURFACTANTS ON THE RATE OF CHEMICAL REACTIONS (Ideal Journal of Multidisciplinary Research, 2026)
Self-organized assemblies such as micelles can change the rates of chemical and enzymatic reactions. Effects of micelles of surfactants on these reactions can be attributed to their electrostatic and hydrophobic interactions with reactants. Surfactants are amphiphilic organic compounds, containing both hydrophobic groups (their tails) and hydrophilic groups (their heads). Thus, a surfactant molecule contains both a water insoluble component and a water soluble component. The tail of most surfactants consists of a hydrocarbon chain. Surfactants are classified into four types. Anionic surfactants, such as sodium dodecyl sulfate (SDS), contain anionic functional groups at their head, that is, sulfate, sulfonate and phosphate.
Keywords: Organic solvents, ionic associates, cation, tetraphenylarsonium, tetraphenylphosphonium, triphenyl lead, ionic association, benzene, toluene, xylene.